Droplet condensation on the patterned surface: molecular dynamics simuation - Goh, Jun Kang (Nanyang Technological University, 2024)
Condensation of carbon dioxide is a critical process in many industrial applications, including thermal management, energy-efficient heat exchangers, cryogenic systems, and carbon capture technologies. In this work, the condensation behaviour of carbon dioxide and associated heat transfer characteristics on solid surfaces were investigated using molecular dynamics simulations under various conditions, including surface properties, cooling temperatures, and pressures. By optimizing the surface interactions, phase transitions among different condensation modes were observed, and three characteristic phases were identified: nucleation, coalescence, and growth. Enhanced surface wettability is expected to accelerate the process of liquid film formation and improve the overall heat transfer process, whereas lower cooling temperatures and higher pressures tend to result in greater condensation through increased supersaturation and molecular collisions. These findings suggest that such a relationship exists among these surface properties and operational parameters to achieve optimum efficiency during condensation. Further research should focus on experimental validation and the application of advanced surfaces for further improvement in industrial processes.